PENINGKATAN LITERASI AI DI KALANGAN MAHASISWA INDONESIA: ANALISIS KEBIJAKAN DAN IMPLEMENTASI - Sianturi, Puput Adelina; Manalu, Nora Ferrety Anggel; Ginting, Selvi Sari Br; M. Joharis, M. Joharis (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The rapid development of artificial intelligence (AI) has significantly transformed various aspects of life, including education. AI is increasingly utilized in academic activities, such as information retrieval, assignment preparation, and data analysis. However, the level of understanding and application among students varies. This study aims to explore the extent of students comprehension and utilization of AI, as well as their perceptions of its impact. This research is based on the theory of technology adoption and digital literacy, which highlight factors influencing the acceptance and use of new technologies in academic settings. A quantitative survey method was employed, involving 36 students from various universities in Indonesia as respondents. Data were collected through a questionnaire comprising nine questions related to students understanding, usage, benefits, and concerns about AI. The findings indicate that 48.3% of respondents agreed and 34.4% strongly agreed that AI provides significant benefits in daily life, particularly in searching for references, preparing reports, and analyzing data. However, 13.8% remained neutral about AIs benefits. Additionally, students from technology-based majors use AI more frequently than those from non-technology majors. While AI is considered helpful, 34.5% of respondents expressed concerns that AI could replace human jobs, whereas 44.8% were worried about potential AI misuse in data security and privacy. These results suggest that while AI is widely accepted in academic settings, there is still a need for further education on its ethical and responsible use. A total of 37.9% of students expressed interest in attending AI training programs to enhance their understanding. Therefore, systematic efforts from educational institutions are required to provide comprehensive AI literacy programs, enabling students to utilize this technology optimally and responsibly in the digital era.